Learning Strategies of Islamic Religious Education Teachers in the Era of the Independent Curriculum - Joko Aji Purnomo; Mukhlisin Mukhlisin (IERA, Islamic Education and Research Academy, 2025)
This study aims to explore the learning strategies employed by Islamic Religious Education (PAI) teachers in the context of the Independent Curriculum (Kurikulum Merdeka) at SMK Negeri 1 Kertosono. With the curriculum being widely introduced across Indonesia, educators must adapt their teaching methods to align with new educational standards. This qualitative research, conducted through participant observation, interviews, and documentation, identifies two primary strategies: Discovery Learning and Project-Based Learning. It also highlights the challenges faced, such as teacher readiness and curriculum implementation at the institutional level, alongside the supportive role of collaborative efforts between school leaders and staff. The study concludes that continuous professional development and utilization of the Merdeka Belajar platform are critical to overcoming these challenges.